Cinematography for ‘To Mum (Love, Me)’ - Nurul Sharmira Shamsudin (2015)
The lesbian, gay, bisexual and transgender (LGBT) culture is an unfamiliar terrain to many living in Singapore, a country that is completely mixed up in terms of traditional and modern values. I would like to think that making this film is me making a contribution to the LGBT society; to team up with the director to help her accomplish her vision, to allow the director/writer to speak up about the struggles of being a gay through a narrative that encompasses these. Among the many struggles an LGBT individual face is gaining acceptance for being gay. We would think that amongst everyone we know it is rightfully easier for immediate family members to be accommodating when a family member admits he or she is gay. For many cases, this does not deem to be true. On that note, To Mum (Love, Me) is not completely a lesbian film. It deals with a mother and a daughter overcoming a conflict in a country where traditional and modern values do not always mix. More than anything else, it is a family drama. The title of the film speaks for itself: a letter to a mother. The director/writer has intended the film to be semi-biographical. Which means it is a personal yet universal story, which the universal audience can relate to or empathise with. This gives me an idea in deciding the tone of the film: realistic, simple and casual. The task of conveying the tone of the film visually is done by adopting a style that is predominantly organic and is not about calling too much attention to itself. Nothing too fanciful to deviate the audience from the biggest and main component of the film: the story that embodies the director/writer’s intention. The goal of the film, cinematography wise, is to create an onscreen realistic environment that aims to evoke a consensus among both heterosexual and homosexual audience.